STUDI PENDAPATAN PENGOLAHAN KOPRA DI DESA TUMBU-TUMBU JAYA KECAMATAN KOLONO TIMUR - Harlinda Harlinda; Muh Yani Balaka; Irmawati P Tamburaka (JEP (Jurnal Ekonomi Pembangunan), 2018)
This study aims to determine copra processing revenue in tumbu-tumbu jaya village, east kolono district, south konawe regency. This type of research is quantitative descriptive. The population of this research is all family heads who work as copra processors in tumbu-tumbu jaya village, east kolono subdistrict, south konawe regency, which are 25 people. The sampling technique in this study was carried out in a census that is overall from the existing population. Data analysis using income analysis. The results of this study conclude that: the total net income obtained by copra processor is rp. 173,478,750/harvest season with an average of rp. 6,939,150/harvest season.